Titanium dioxide nanoparticles (TiO2 NPs) promote growth and ameliorate salinity stress effects on essential oil profile and biochemical attributes of Dracocephalum moldavica - Gohari, Gholamreza; Mohammadi, Asghar; Akbari, Ali; Panahirad, Sima; Dadpour, Mohammad Reza; Fotopoulos, Vasileios; Kimura, Seisuke (My University, 2020)
Considering titanium dioxide nanoparticles (TiO2 NPs) role in plant growth and especially in plant tolerance against abiotic stress, a greenhouse experiment was carried out to evaluate TiO2 NPs effects (0, 50, 100 and 200 mg L-1) on agronomic traits of Moldavian balm (Dracocephalum moldavica L.) plants grown under different salinity levels (0, 50 and 100 mM NaCl). Results demonstrated that all agronomic traits were negatively affected under all salinity levels but application of 100 mg L-1 TiO2 NPs mitigated these negative effects. TiO2 NPs application on Moldavian balm grown under salt stress conditions improved all agronomic traits and increased antioxidant enzyme activity compared with plants grown under salinity without TiO2 NP treatment. The application of TiO2 NPs significantly lowered H2O2 concentration. In addition, highest essential oil content (1.19%) was obtained in 100 mg L-1 TiO2 NP-treated plants under control conditions. Comprehensive GC/MS analysis of essential oils showed that geranial, z-citral, geranyl acetate and geraniol were the dominant essential oil components. The highest amounts for geranial, geraniol and z-citral were obtained in 100 mg L-1 TiO2 NP-treated plants under control conditions. In conclusion, application of 100 mg L-1 TiO2 NPs could significantly ameliorate the salinity effects in Moldavian balm.
Keywords: Nanoparticles; Plants; Seedling growth